Disparities in Child Health A Solutions-Based Approach - Lopez, Michelle A. (SpringerBriefs in Child Health,, 2018)
This forward-looking resource shines needed light on-and offers realistic solutions for eliminating-health disparities affecting one of the most vulnerable populations: children. Its multilevel framework identifies sources of pediatric health inequities in developmental, societal, familial, financial, and service delivery contexts and sets out innovations for breaking down and addressing longstanding concerns. Plentiful opportunities are described for reducing gaps and promoting equity at various service platforms, from locally-based improvements to systemwide tech upgrades, that can be used as models for revamping larger health policy. And the authors' long-term perspective emphasizes screening, wellness care, early intervention, and prevention strategies to support young patients in the transitions between childhood, adolescence, and young adulthood. Included in this compact idea book: Disparities in child health: a review Quality of care in pediatrics and health disparities: the increasing role of quality improvement science Community health worker interventions Technology-based interventions to address pediatric health disparities Place-based strategies in promoting health equity Future directions for a solutions-based approach With its clear delineation of issues and priorities, and its workable recommendations for addressing them, Disparities in Child Health is a ready source of ideas and advocacy for practitioners and researchers in pediatrics, maternal and child health, and general practice/family medicine.